A Bumpy Ride of Mycobacterial Phagosome Maturation: Roleplay of Coronin1 Through Cofilin1 and cAMP - Saha, Saradindu; Hazra, Arnab; Ghatak, Debika; Singh, Ajay Vir; Roy, Sadhana; BoseDasgupta, Somdeb (Frontiers in Immunology, 2021)
Phagosome-lysosome fusion in innate immune cells like macrophages and neutrophils marshal an essential role in eliminating intracellular microorganisms. In microbe-challenged macrophages, phagosome-lysosome fusion occurs 4 to 6 h after the phagocytic uptake of the microbe. However, live pathogenic mycobacteria hinder the transfer of phagosomes to lysosomes, up to 20 h post-phagocytic uptake. This period is required to evade pro-inflammatory response and upregulate the acid-stress tolerant proteins. The exact sequence of events through which mycobacteria retards phagolysosome formation remains an enigma. The macrophage coat protein Coronin1(Cor1) is recruited and retained by mycobacteria on the phagosome membrane to retard its maturation by hindering the access of phagosome maturation factors. Mycobacteria-infected macrophages exhibit an increased cAMP level, and based on receptor stimulus, Cor1 expressing cells show a higher level of cAMP than non-Cor1 expressing cells. Here we have shown that infection of bone marrow-derived macrophages with H37Rv causes a Cor1 dependent rise of intracellular cAMP levels at the vicinity of the phagosomes. This increased cAMP fuels cytoskeletal protein Cofilin1 to depolymerize F-actin around the mycobacteria-containing phagosome. Owing to reduced F-actin levels, the movement of the phagosome toward the lysosomes is hindered, thus contributing to the retarded phagosome maturation process. Additionally, Cor1 mediated upregulation of Cofilin1 also contributes to the prevention of phagosomal acidification, which further aids in the retardation of phagosome maturation. Overall, our study provides first-hand information on Cor1 mediated retardation of phagosome maturation, which can be utilized in developing novel peptidomimetics as part of host-directed therapeutics against tuberculosis.